Uncompromising Activist : Richard Greener, First Black Graduate of Harvard College - Chaddock, Katherine Reynolds, 1945- (Book collections on Project MUSE., 2017)
"Richard Theodore Greener (1844-1922) was a renowned black activist and scholar. In 1870, he was the first black graduate of Harvard College. During Reconstruction, he was the first black faculty member at a Southern white college, the University of South Carolina. He was even the first black US diplomat to a white country, serving in Vladivostok, Russia. A notable speaker and writer for racial equality, he also served as a dean of the Howard University School of Law and as the administrative head of the Ulysses S. Grant Monument Association. Yet he died in obscurity, his name barely remembered. His black friends and colleagues often looked askance at the light-skinned Greener's ease among whites and sometimes wrongfully accused him of trying to 'pass.' While he was overseas on a diplomatic mission, Greener's wife and five children stayed in New York City, changed their names, and vanished into white society. Greener never saw them again. At a time when Americans viewed themselves simply as either white or not, Greener lost not only his family but also his sense of clarity about race. Richard Greener's story demonstrates the human realities of racial politics throughout the fight for abolition, the struggle for equal rights, and the backslide into legal segregation. Katherine Reynolds Chaddock has written a long overdue narrative biography about a man, fascinating in his own right, who also exemplified America's discomfiting perspectives on race and skin color. Uncompromising Activist is a lively tale that will interest anyone curious about the human elements of the equal rights struggle"--Provided by publisher.